The Influence of Increased Understanding Through Direct Interaction Strategies on Class XI Students in Reading Instruction at SMK Telkom 2 Medan - Tamilan, Susmita; Pangaribuan, Darman (LPPPI Publishing, 2025)
This study investigates the effect of Direct Interaction Strategy on enhancing reading comprehension among Grade XI students at SMK Telkom 2 Medan. Reading comprehension is a fundamental skill in vocational education, yet many students continue to struggle with understanding texts due to low motivation and the use of passive instructional strategies. To address this issue, this research applies the Direct Interaction Strategy, which promotes structured, student-centered learning through active engagement, peer collaboration, and continuous feedback. A quasi-experimental quantitative design was employed, involving two groups: an experimental class taught using the Direct Interaction Strategy, and a control class taught with traditional methods. Pre-tests and post-tests were administered to assess students' comprehension before and after the intervention. The findings reveal a significant improvement in the reading scores of students in the experimental group, with an average increase of 31.92 points, compared to only 4.4 points in the control group. The results of the t-test analysis (t =5.40) confirm that the improvement was statistically significant. These findings suggest that the Direct Interaction Strategy is an effective instructional method for improving students’ reading comprehension. This study contributes theoretically by strengthening the understanding of interactive teaching methods and offers practical implications for educators seeking to improve literacy outcomes in vocational school settings.